To Identify Anti-competitive practices in Tourism Market,: Case study: Market of Tehran's travel and tourism services - Ommolbanin Rezakhani; Zahra Nadalipour; Mina Hosseini (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2021)
Anti-competitive practices in the tourism market can be examined from two perspectives of marketing and competition law. Despite the importance of the issue, little attention has been paid to it, and only a few relevant studies have been conducted in Iran. The present study examines the anti-competitive practices in the travel and tourism services market in Iran and particularly among Tehran's travel agencies. To conduct this research, a semi-structured interview method, one of the important qualitative research tools, has been used. The statistical population of the research includes managers and experts in the field of tourism services and experts in the field of competition and competition law. By using the interpretive analysis method, the content of interviews has been reviewed and analyzed. According to the objectives of the research and coding process, the components were extracted and explained. The results indicate that there are instances of unilateral and multilateral anti-competitive practices in the market under study. The intensity of these procedures varies depending on being a retailer or wholesaler. Finally, several recommendations have been made. IntroductionIn the past, for various reasons, including increased demand for supply and limited competition in various fields, the demands and needs of customers were not paid much attention, and people were forced to choose and receive the goods and services they need with any quality. However, today, due to the increased number of suppliers and customers and the formation of competition of production and service organizations to survive and increase profitability and market share, it is forced to provide more diverse goods and services. In this regard, competition was formed among suppliers to provide better quality goods or services. Researchers believe that high quality and customer satisfaction levels lead to customer loyalty; this is especially true in the service industry (Hossain and Leo, 2009). Large tour operators and travel agencies are among the main players of the travel distribution system. Large tour operators can take away the tourism market from their neighbors by forcing them to sign exclusive agreements. Thus, smaller agencies face serious barriers to entering the market and do not have the power to establish a new agency and are forced to exit the market (Papatheodoro, 2003). For shaping fair competition in the tourism industry, regulatory tools are needed, and competition law can take the market situation out of Monopoly by creating conditions for fair competition. The Competition Law sub-section deals with anti-competitive practices, including unilateral and collective agreements (vertical and horizontal agreements) and disruptive mergers, each of which is an example of behavior that causes. They disrupt market competition. Competition to improve service quality is generally recognized as a key strategic issue for organizations operating in the service sector. Organizations that achieve a higher level of service quality will have higher levels of customer satisfaction as a prelude to achieving a sustainable competitive advantage (Guo et al., 2008). Today, Iran's tourism industry, like other industries, needs competition to increase quality and efficiency. Therefore, the main question of the present study is to what extent the issue of competition has been formed healthily and fairly among the existing tourism businesses? And if there are anti-competitive forces and procedures in the tourism market? The present study seeks to know what these procedures are. Materials and MethodsThe present study is descriptive. The statistical population consists of both managers and experts in travel agencies and professors in the relevant field. All interviewees have had either university education or experiences in the field of travel and tourism services. By using two judgment and snowball sampling methods, 14 people were selected as a sample. The criterion for selecting this number of samples was to achieve saturation. The average interview time was one hour. In this study, due to the impossibility of gathering experts simultaneously in a joint meeting, the interview method was chosen. Interviews were recorded, written, and coded. Semi-structured interviews were used, and the data obtained from the interviews were analyzed using thematic analysis. Discussion and ResultsBased on the research findings and according to the content analysis map that was extracted and discussed, the results can be mentioned as follows:Given the "use of dominant position," which is one of the unilateral anti-competitive procedures, factors such as technology, and the emergence of startups and the elimination of intermediaries have changed the face of competition among activists in the travel and tourism services in Tehran. On the other hand, managerial problems and the entry of the public sector as a strong competitor for private sector activists are mentioned as a challenge by activists in this field. From the perspective of the anti-competitive practice of "price distortion," the nature of being seasonal is one of the reasons mentioned, which has led to the formation of unconventional discounts and unregulated auctions in this sector. On the other hand, Monopoly is one example of "price disruption" among the agencies under study, both in terms of service nature and aggressive pricing. Another challenging issue for activists is their concern about rent, which significantly impacts competitive mechanisms in this market in terms of both communication and power. On the other hand, due to the anti-competitive practice of "disrupting the transaction, " the interviewees listed factors such as lack of supervision, customer type and Monopoly, and believe that circumventing the rules shows weakness and inefficiency of existing laws, has fueled anti-competitive instances. Customers, depending on the type of relationship they have with the organization (permanent and loyal or temporary, with different social and economic classes and their level of awareness of services), also have a significant impact on decision-making that can enrich antitrust procedures. On the other hand, the influence of charterers is also an issue that should not be overlooked. Another important factor in unilateral anti-competitive practices is the way of governing in this field are as follows, all challenges directly or indirectly address the quality of governance: illegal activities, the inefficiency of standards, lack of support from brokers, lack of experts among relevant authorities, lack of a well-codified plan, and the lack of continuous oversight. On vertical collective antitrust practices, issues, as follows, have been mentioned: such as "environmental factors" in the form of the seasonal nature of industry and sanctions; "monopoly" due to the specialized nature of the routes that in some cases have made Monopoly inevitable; "chartering collusion" with airlines so that others are unable to compete with them and it has become impossible to control ticket prices on some charters (which may eventually lead to the loss of passengers' rights); "wholesale cooperation with individuals "; and "comparative and competitive advantages," which have led to the distinction, specialization, and type of Monopoly. Here, management and governance are of great importance, as examples such as economic rents, lack of standards and managerial inefficiency, the formation of anti-competitive examples, and collusion among monopolists.Regarding horizontal collective anti-competitive practices, for reasons such as agencies' unwillingness to cooperate in groups, low power, large numbers, and the entry of the public sector and support for monopolies, it is impossible to form collusion among retail agencies. However, among wholesalers, there is a potential for Monopoly, which their influence and power can exemplify in setting prices, eliminating retailers, and aligning with the policies of other wholesalers. And limited and constant supply capacity of some products and services has paved the way for Monopoly as much as possible. ConclusionsToday, due to changes in the travel and tourism services market, including reducing problems and barriers to entry and the emergence of new entrants to this market, we are witnessing a relatively significant competition among businesses providing travel and tourism services. Also, the presence of e-agencies in cyberspace with irrational discounts and sometimes tour operators' direct sales has increased the pressures of competition for travel and tourism agencies and has led to bankruptcy. In addition, technology has made tourists more inclined to travel independently and with personal planning, which will affect the performance and profitability of agencies. On the other hand, competition in the tourism industry has a dynamic meaning, which has led to some anti-competitive practices. But business owners and sometimes customers are not aware of these anti-competitive practices. They do not know that this issue can be investigated within the legal framework and can be followed up. Examining the practical procedure of the Competition Council ,  the cases raised since the establishment of the Competition Council in this institution also show that travel agencies have not yet complained about the violation of market competition. It is noteworthy that the Competition Council, in its report on various markets, has not yet examined the possibility of anti-competitive practices in the tourism market. However, despite the lack of practice, the present study results indicate that there are competitive concerns about the tourism market. The majority of the interviewees mentioned the existence of an anti-competitive approach acknowledged "in many cases this also affects supply and demand." As a result, in analyzing the results of this research, it should be said that not only there is a dominant position, but there are also signs of abuse of a dominant position in this market. On the other hand, unlike the European legislature, the view of the Iranian legislature does not limit unilateral anti-competitive practices to dominant economic enterprises. However, in the tourism market, based on the data of the present study, it can be seen that the implementation of unilateral anti-competitive procedures by firms with a dominant position does not lead to the reaction of the competition regulator. There is evidence in this study that aggressive pricing, restricting resale, transaction discrimination, and misleading statements are alarm bells that the Competition Council should take seriously.